2015
DOI: 10.1007/s00436-014-4272-3
|View full text |Cite
|
Sign up to set email alerts
|

Redefinition of Nosema pyrausta (Perezia pyraustae Paillot 1927) basing upon ultrastructural and molecular phylogenetic studies

Abstract: Populations of European corn borer (Ostrinia nubilalis Hübner) from Krasnodar Territory (Southwestern Russia) become regularly infected with Nosema-like microsporidia. To identify the parasite, it was subjected to electron microscopy and small subunit ribosomal RNA (SSU rRNA) gene sequencing. The spore ultrastructure of the parasite was highly similar to Nosema bombycis from China and Nosema pyrausta from the USA. The nucleotide sequence of SSU rRNA gene was identical to a microsporidium isolated from O. nubil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The use of primers flanking full-length gene of N. bombycis (Table 1) allowed amplification of this locus in N. bombycis, N. tyriae and N. pyrausta, that is expectable given that these three taxa are closely related and their SSU rRNA gene sequences are 99.7–99.8% similar (Tokarev et al ., 2015). The nucleotide sequence of N. bombycis was 100% identical to that of N. bombycis from B. mori (sampled in China) available at Genbank (# EOB11276).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of primers flanking full-length gene of N. bombycis (Table 1) allowed amplification of this locus in N. bombycis, N. tyriae and N. pyrausta, that is expectable given that these three taxa are closely related and their SSU rRNA gene sequences are 99.7–99.8% similar (Tokarev et al ., 2015). The nucleotide sequence of N. bombycis was 100% identical to that of N. bombycis from B. mori (sampled in China) available at Genbank (# EOB11276).…”
Section: Resultsmentioning
confidence: 99%
“…HK showed clear differentiation between N.bombycis , N. pyrausta and N. tyriae that would be problematic if SSU rRNA was compared in these species due to the very low level of divergence of the latter locus (Tokarev et al ., 2015). Nosema antheraeae is more diverged in its SSU rRNA gene sequence from N. bombycis than N. tyriae and N. pyrausta and this is fairly reflected by differences in their HK gene sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spores of the microsporidium used for experimental infection in this study were identified using SSU rRNA gene sequencing as N. pyrausta (Tokarev et al, 2015). When infected with an average dosage of 10 5 fresh spores per larva, the second instar treatment group (Lii) of O. nubilalis showed a median lethal time (LT 50 ) of 15.2 AE 1.27 days (mean AE SE) and 100% larval mortality, corresponding to 0% pupation success.…”
Section: Resultsmentioning
confidence: 99%
“…Nosema pyrausta [ 21 ] was propagated in a temporary laboratory culture of the European corn borer, Ostrinia nubilalis Hbn, which is the typical host of this parasite. The larvae were maintained on an artificial diet [ 22 ] and infected with N. pyrausta spores according to Tokarev et al [ 15 ].…”
Section: Methodsmentioning
confidence: 99%